2021
DOI: 10.7150/ijms.54644
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Ocimum gratissimumAqueous Extracts on HaCaT Cells Against UVC-Induced Inhibition of Cell Viability and Migration

Abstract: Ultraviolet C (UVC) has been applied to treatment of infections in wounds for at least the last two decades, however, cells being treated can be damaged if exposure is prolonged, which calls for protective measures, such as drug or herbal pre-treatment, to minimize damage. Ocimum gratissimum contains plant polyphenols such as isoflavones and caffeic acid, which have antioxidant effects. We hypothesize that Ocimum gratissimum aqueous extracts (OGE) can inhibit UVC-induced oxidative damage on skin cells. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 48 publications
(62 reference statements)
0
11
0
Order By: Relevance
“… Chang et al. (2021) reported that 100 μg/mL O. gratissimum restored cell activity and protected against ultraviolet C-induced inhibition of cell proliferation and migration of skin cells, and therefore can serve as a potent natural wound care agent.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“… Chang et al. (2021) reported that 100 μg/mL O. gratissimum restored cell activity and protected against ultraviolet C-induced inhibition of cell proliferation and migration of skin cells, and therefore can serve as a potent natural wound care agent.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…There were some reports related to wound healing-related cell migration induced by herbal extracts, such as Ocimum gratissimum extract (17) and Coccinia grandis extract.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid peroxidation in the cell is a common detrimental outcome of free radicals (FRs) that end up decreasing the membrane potential and cell damage. Malondialdehyde (MDA) causes severe cell injury via stimulation of polymerization and cross linking in components of the membrane [5]. FRs react with DNA and produce 8-hydroxyguanine (8-OHGua) that is the destructive product of DNA [6].…”
Section: Introductionmentioning
confidence: 99%